Life in the garden - Lively, Penelope, 1933- (Viking, 2018)
"From the Booker Prize winner and national bestselling author, reflections on gardening, art, literature, and life. Penelope Lively takes up her key themes of time and memory, and her lifelong passions for art, literature, and gardening in this philosophical and poetic memoir. From the courtyards of her childhood home in Cairo to a family cottage in Somerset, to her own gardens in Oxford and London, Lively conducts an expert tour, taking us from Eden to Sissinghurst and into her own backyard, traversing the lives of writers like Virginia Woolf and Philip Larkin while imparting her own sly and spare wisdom. "Her body of work proves that certain themes never go out of fashion," writes the New York Times Book Review, as true of this beautiful volume as of the rest of the Lively canon. Now in her eighty-fourth year, Lively muses, "To garden is to elide past, present, and future; it is a defiance of time." "--